2013
DOI: 10.2337/dc12-1330
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Wearing Prescription Custom-Made Footwear in Patients With Diabetes at High Risk for Plantar Foot Ulceration

Abstract: OBJECTIVEPrescription custom-made footwear can only be effective in preventing diabetic foot ulcers if worn by the patient. Particularly, the high prevalence of recurrent foot ulcers focuses the attention on adherence, for which objective data are nonexisting. We objectively assessed adherence in patients with high risk of ulcer recurrence and evaluated what determines adherence.RESEARCH DESIGN AND METHODSIn 107 patients with diabetes, neuropathy, a recently healed plantar foot ulcer, and custom-made footwear,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
195
1
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(248 citation statements)
references
References 26 publications
18
195
1
11
Order By: Relevance
“…This low level of foot care behavior identified by this study corroborates previous research that revealed inadequacies of foot care practice, and indicated that the majority of patients fail to get the appropriate size of footwear, and they do not inspect inside their footwear or indeed inspect their feet sufficiently (Waaijman, 2013). In this respect, Bell et al (2005) reported that the degree to which a person is able to perform diabetes foot self-care is likely to be influenced by a number of factors, including personal health, access to medical care and foot care education, and formal and informal support.…”
Section: Discussionsupporting
confidence: 73%
“…This low level of foot care behavior identified by this study corroborates previous research that revealed inadequacies of foot care practice, and indicated that the majority of patients fail to get the appropriate size of footwear, and they do not inspect inside their footwear or indeed inspect their feet sufficiently (Waaijman, 2013). In this respect, Bell et al (2005) reported that the degree to which a person is able to perform diabetes foot self-care is likely to be influenced by a number of factors, including personal health, access to medical care and foot care education, and formal and informal support.…”
Section: Discussionsupporting
confidence: 73%
“…In other words, prescribed footwear can only be effective in preventing DFUs if worn by the patient. 37 Several studies have suggested that high risk patients wear their prescribed footwear during only 15-28% of their total daily activities. [38][39][40] While education could play an important role in enhancing patient adherence to prescribed footwear, 41 recent studies suggest that without frequent education, the adherence could be diminished over time.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, patients were classified based on a measured in-shoe peak pressure ,200 kPa (15,27,28) and adherence .80% (29). This parameter, WP, and CPTS were included in the analysis.…”
Section: Independent Risk Factorsmentioning
confidence: 99%